МАКРОМАРКЕТИНГ КАК ИНСТРУМЕНТ ГОСУДАРСТВЕННОГО РЕГУЛИРОВАНИЯ В ПРОМЫШЛЕННОЙ СФЕРЕ. - Бекмурзаев, Б. Б. (Journal of Economic Research & Business Administration, 2015)
Макромаркетингтiң кешенi – ұлттық экономика дамуының тиiмдi аспаптарының бiрi. Қазақстандық үкiмет кейбiр макромаркетингтiң бiр бөлiктерiн қолданады, бiрақ біздің елде бiртұтас макромаркетинг жиынтығының тиiмдi қолдануы туралы айту әлi ерте. *** Complex of macromarketing is one of the most efficient instruments of developing national economics. Kazakh government uses some parts of macromarketing, but it is too early to speak about efficient use of whole macromarketing complex in our country.